Molecular detection of Coxiella spp. in ticks (Ixodidae and Argasidae) infesting domestic and wild animals: with notes on the epidemiology of tick-borne Coxiella burnetii in Asia - Ali, Abid; Obaid, Muhammad Kashif; Almutairi, Mashal M.; Alouffi, Abdulaziz; Numan, Muhammad; Ullah, Shafi; Rehman, Gauhar; Islam, Zia Ul; Khan, Sher Bahadar; Tanaka, Tetsuya (Frontiers in Microbiology, 2023)
Tick-borne Coxiella spp. are emerging in novel regions infecting different hosts, but information regarding their occurrence is limited. The purpose of this study was the molecular screening of Coxiella spp. in various ticks infesting goats, sheep, camels, cattle, wild mice, and domestic fowls (Gallus gallus domesticus) in various districts of Khyber Pakhtunkhwa, Pakistan. Morphologically identified tick species were confirmed by obtaining their cox1 sequences and molecularly screened for Coxiella spp. by sequencing GroEL fragments. Almost 345 out of 678 (50.9%) hosts were infested by nine tick species. Regarding the age groups, the hosts having age greater than 3 years were highly infested (192/345, 55.6%), while gender-wise infestation was higher in female hosts (237/345, 68.7%). In collected ticks, the nymphs were outnumbered (613/1119, 54.8%), followed by adult females (293/1119, 26.2%) and males (213/1119, 19.7%). Total of 227 ticks were processed for molecular identification and detection of Coxiella spp. The obtained cox1 sequences of nine tick species such as Hyalomma dromedarii, Hyalomma anatolicum, Haemaphysalis cornupunctata, Haemaphysalis bispinosa, Haemaphysalis danieli, Haemaphysalis montgomeryi, Rhipicephalus haemaphysaloides, Rhipicephalus microplus, and Argas persicus showed maximum identities between 99.6─100% with the same species and in the phylogenetic tree, clustered to the corresponding species. These ticks were found positive for Coxiella spp. (40/227, 17.6%), including Coxiella burnetii (15/40, 6.7%), Coxiella endosymbionts (14/40, 6.3%), and different Coxiella spp. (11/40, 4.9%). By the BLAST results, the GroEL fragments of Coxiella spp. showed maximum identity to C. burnetii, Coxiella endosymbionts and Coxiella sp., and phylogenetically clustered to the corresponding species. This is the first comprehensive report regarding the genetic characterization of Coxiella spp. in Pakistan's ticks infesting domestic and wild hosts. Proper surveillance and management measures should be undertaken to avoid health risks.